2021
DOI: 10.3390/su132212356
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Models Founded on Soil Characteristics for the Estimated Uptake of Nine Metals by Okra Plant, Abelmoschus esculentus (L.) Moench., Cultivated in Agricultural Soils Modified with Varying Sewage Sludge Concentrations

Abstract: Prediction models were developed to estimate the extent to which the metals Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, and Zn were taken up by the fruits, the leaves, the stems, and the roots of the okra plant, Abelmoschus esculentus (L.) Moench., grown under greenhouse conditions in soil modified with a spectrum of sewage sludge concentrations: 0, 10, 20, 30, 40, and 50 g/kg. All the metals under investigation, apart from Cd, were more concentrated in the A. esculentus roots than in any other organ. Overall, the sum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…In the present research, R 2 exhibited a positive association with ME and a negative relationship with MNAE and MNB. Comparable data were published with respect to grain sorghum and okra species grown in field soil combined with SS (Eid et al 2021c;Shaltout et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the present research, R 2 exhibited a positive association with ME and a negative relationship with MNAE and MNB. Comparable data were published with respect to grain sorghum and okra species grown in field soil combined with SS (Eid et al 2021c;Shaltout et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…of net metal element absorbed by A. bisporus during its vegetative growth, β indicates the regression coefficients, pH C and OC C are the pH and organic carbon (mg/kg) of the casing material, while ME S+C indicates the sum of metal elements present in the mushroom substrate and casing material, respectively. Besides this, the constructed models were validated using two different validation tools, viz., model efficiency (ME) and root mean square error (RMSE), as suggested by Eid et al [44].…”
Section: Bioaccumulation Factor and Prediction Modeling Of Metal Elem...mentioning
confidence: 99%
“…Thus, the mixing rate of SS greatly contributed to increasing the levels of various nutrients and metal elements in the casing material. Previously, Eid and coworkers [44] determined the physiochemical and metal element properties of SS and reported that SS had significant levels of various nutrients, which were further useful for increasing the soil fertility under Abelmoschus esculentus crop cultivation.…”
Section: Characteristics Of the Mushroom Substrate And Casing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the upper trophic strata, their presence becomes biomagnified and can give rise to a number of chronic pathologies in both humans and animals [3]. Exposure to toxic metals typically occurs through the ingestion of contaminated products within the diet, the immediate consumption of soil or polluted drinking water, and the inhalation of air particle suspensions [4].…”
Section: Introductionmentioning
confidence: 99%